2003
DOI: 10.2355/isijinternational.43.1502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water-Gas Shift Reaction on Reduction of Iron Oxide Powder Packed Bed with H2-CO Mixtures

Abstract: Although the hydrogen reduction is thermally more disadvantageous than the CO reduction, it is advantageous that the reduction rate with H 2 is much larger than that with CO. In order to examine the effective use of hydrogen, the reduction of FeO 1.05 powder packed bed with H 2 -CO mixture was conducted, and the results were analyzed by a proposed model. The temperature, at which the reduction equilibria of FeO 1.05 with H 2 and CO equal, is determined to be 1 093 K from the present results. The apparent rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…They found that the rate of reduction decreased as the concentration of CO increased in the gas mixture. Lin et al 8) 9) used the Rist's model to study the effect of water-gas shift reaction on the reduction of iron oxide powder packed bed with H 2 -CO mixtures.…”
Section: Szekelymentioning
confidence: 99%
“…They found that the rate of reduction decreased as the concentration of CO increased in the gas mixture. Lin et al 8) 9) used the Rist's model to study the effect of water-gas shift reaction on the reduction of iron oxide powder packed bed with H 2 -CO mixtures.…”
Section: Szekelymentioning
confidence: 99%
“…Blending of coke with HDPE therefore promotes the generation of hydrogen in the reaction environment. Hydrogen gas, apart from being a faster reducing agent than both carbon monoxide and solid carbon (Sohn and Fruehan, 2005;OnoNakazato et al, 2003), also enhances the rate of reduction of iron oxides by carbon monoxide (Ono-Nakazato et al, 2003)when it is added to a reaction system containing the latter.…”
Section: Fraction Reacted As a Function Of Timementioning
confidence: 99%
“…However, most of the work has been done with pellets, briquettes, and iron oxide powder beds and thus at temperatures below ~1 400 K. [3][4][5][6][7][8] Much less work has been performed on the reduction rate of fine magnetite concentrate particles with mixtures of H2 and CO at temperatures above 1 473 K to be used in the process under development.…”
Section: Introductionmentioning
confidence: 99%